Environmental and health benefits of establishing a coal banning area in the Beijing-Tianjin-Hebei region of China. (15th February 2021) - Si, Ruirui; Xin, Jinyuan; Zhang, Wenyu; Wen, Tianxue; Li, Shihong; Ma, Yining; Wu, Xinrui; Cao, Yukun; Xu, Xiaojuan; Tang, Hairong; Xu, Jing; Li, Xingru; et al.
Abstract: In 2017, a coal banning area of approximately 10, 000 square kilometers was established in the Beijing-Tianjin-Hebei (BTH) region of China for the first time. This study compared the change of elemental concentrations during the autumn and winter of 2016 and 2017, and analyzed the environmental and health benefits of the coal banning policy. Result showed that compared to 2016, the reduction rate of atmospheric particulate matter with an aerodynamic diameter no larger than 2.5 μm (PM2.5 ) in 2017 was as high as 63.5% (p < 0.01), and that of the total elements in PM2.5 was up to 43% (p < 0.01). Coal consumption, transportation, industry, soil dust, and fuel consumption were the main sources of these elements in BTH. Coal consumption and industry accounted for 5.8–26.2% and 6.5–31.3%, respectively, of the total elements. After the coal banning area was established, the elements from coal consumption were reduced by 13.5–60.3% (the background station was reduced by 19.6%, p < 0.05), and those from industrial sources were reduced by 11–80.1%. The results of the health risk assessment showed that the carcinogenic risk of the coal consumption and industrial sources had been reduced by 30.7–48.3% in 2017. The policy of the coal banning is very effective in controlling the air pollution in urban agglomeration in developing countries and has resulted in great health and environmental benefits. Graphical abstract: Image 1 Highlights: Coal Banning Area is the most efficient pollution control measure in BTH in 2017. The measure cut down the bulk coal consumption by 10.2% in the 10, 000 km 2 region. The measure has resulted in the high benefits of environment and health in BTH. PM2.5 and total elements declined drastically by 63.5% and 43% in 2017. The carcinogenic risk index of hazardous elements decreased by 36.3% in BTH.